Effect of varicocele repair on conventional sperm parameters in infertile patients with clinical varicocele: A systematic review and metaanalysis. - Agarwal, Ashok; Cannarella, Rossella; Saleh, Ramadan; Boitrelle, Florence; Hamoda, Taha Abdel-Meguid; Gül, Murat; Salvio, Gianmaria; Shah, Rupin (Elsevier Science Inc., 2022)
Objective Varicocele is present in almost 35-40% of men presenting with primary infertility. Despite the significant role of varicocele in the pathogenesis of male infertility, the impact of varicocele repair (VR) on conventional semen parameters remains controversial. To the best of our knowledge, only a few systematic reviews and meta-analyses (SRMA) have evaluated the impact of VR on sperm concentration, total motility, and progressive motility using a before-after analytic approach for analyzing 22, 17, and 5 prospective uncontrolled trials, respectively. Indeed, the majority of SRMAs have focused on pregnancy rate as an outcome. This study aimed to evaluate the effect of VR on conventional semen parameters in infertile patients with clinical varicocele compared to untreated controls. Materials and Methods Literature search was performed in Scopus, PubMed, Ovid, Embase, and Cochrane databases using the PICO model (Population: Infertile patients with clinical varicocele; Intervention: Varicocele repair; Comparison: No treatment; Outcomes: Sperm concentration, sperm total count, sperm progressive motility, sperm total motility, and semen volume). Both randomized-controlled trials (RCTs) and observational studies were included. Results 1632 abstracts were initially assessed for eligibility. 16 studies were finally included with a total of 2420 infertile patients with clinical varicocele (1424 patients treated with VR vs. 996 untreated controls). The analysis showed significantly improved post-operative sperm parameters in the VR group compared to controls: sperm concentration [standardized mean difference (SMD) 1.87 (95% CI: 1.25, 2.48); p<0.01; I 2 =97.6%], total sperm count [SMD 1.89 (95% CI: 0.57, 3.22); p<0.05; I 2 =97.8%], sperm progressive motility [SMD 3.30% (95% CI: 2.16, 4.44); p<0.01; I 2 =98.4%], total sperm motility [SMD 0.89% (95% CI: 0.04, 1.74); p=0.04; I 2 =97.4%] and normal sperm morphology [SMD 1.68% (95% CI: 0.88, 2.47); p<0.05; I 2 =97.4%]. All the outcomes had a high level of inter-study heterogeneity, but sensitivity analysis showed that no study was sensitive enough to change these results. Publication bias was present only in the analysis of sperm concentration and progressive motility. No significant difference was found in semen volume [SMD 0.13 ml (95% CI: -0.24, 0.87); p=0.27; I 2 =89.7%].
Keywords: Infertile Patients; Conventional Sperm Parameters; Varicocele Repair